METACOGNITIVE READING STRATEGIES AWARENESS IN ENGLISH LANGUAGE CONTEXT AMONG AVIATION CADETS - Ismi Syahidah; Nunung Suryati; Siti Muniroh (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2023)
reading in the English language context has widely taken a position in the educational field, the reading score among aviation cadets was far from expectation. Several empirical studies have underpinned metacognitive reading strategies as supporting components in determining the reading performance of EFL learners, yet an investigation within the scope of cadets of the aviation field remains limited in the Indonesian context. This study explored cadets’ awareness level of metacognitive reading strategies and how they demonstrate awareness toward the use of those strategies in the English language context. An explanatory design was utilized, with 30 aviation cadets involved. The data was obtained from self-inventory reports and open-ended questions. The result confirmed that aviation cadets are metacognitively aware of the three elements of reading strategies with medium level of awareness. Moreover, cadets with high scores reading tests encompass more support reading strategies and problem-solving strategies compared to lower scorers. While cadets who got average scorers utilize three parts metacognitive reading strategies. These results confirmed that cadets who can maintain their cognition and proceed with various strategies in reading activities, will perform better in reading within the English language context.